GAMIFIKASI DALAM PEMBELAJARAN AL-QUR'AN DAN HADITS DI MADRASAH ALIYAH: MENINGKATKAN MOTIVASI DAN PARTISIPASI SISWA - Miranda, Andi; Rahmawati, Seli; Adiyono, Adiyono (STIT Ibnu Rusyd Tanah Grogot, 2024)
Learning Al-Qur'an and Hadith in Paser State Aliyah Madrasah (MAN) often faces challenges related to low student motivation and participation. The conventional methods used today are not able to optimally attract students' interest. This study aims to explore the effectiveness of gamification in learning Al-Qur'an and Hadith at MAN Paser, with a focus on increasing student motivation and participation. This research methodology uses a qualitative approach, with data collection techniques through interviews, and observation. Qualitative analysis was used to understand students' experiences and perceptions as well as factors that support and hinder the implementation of gamification. The results showed that the implementation of gamification in learning Al-Qur'an and Hadith significantly increased students' motivation and participation. Gamification elements such as points, badges, leaderboards and daily challenges proved effective in creating a more engaging and interactive learning environment. Factors supporting the implementation of gamification include technological support, teacher engagement, and game design that is relevant to the learning material. However, there are also some barriers such as limited access to technology for some students and training needs for teachers. This study concludes that gamification can be an effective strategy to increase students' motivation and participation in learning Al-Qur'an and Hadith at MAN Paser. Practical recommendations for further development include improving technology access, teacher training, and customizing gamification design according to the local context. The results of this study are expected to contribute to improving the quality of Qur'an and Hadith learning in madrasah as well as being a reference for policy makers in integrating technological innovations in education.